Addition of acidifier with inulin and papain enzyme in the ration towards leukocyte differential in bottle growth period - I, Marhaeni; Yunianto, V. D.; Krismiyanto, L. (Journal of Smart Agriculture and Environmental Technology, 2023)
The aim of the study was to examine the effect of adding acidifier with inulin and papain enzymes in the ration on the differential leukocytes in turkeys during the growth period. The research material consisted of 80 male turkeys aged 12 weeks with an average weight of 1165 ± 62.24 g, an acidifier consisting of a mixture of lactic acid, propionic acid, and formic acid, and inulin sourced from dahlia tuber extract and the enzyme papain. The feed ingredients used in this study were corn, soybean meal, fish meal, rice bran, premix, CaCO3, lysine, and methionine. The research design used a completely randomized design with 5 treatments and 4 replications. The treatments applied included T0 (control diet/RK), T1 (RK + 1% acidifier), T2 (RK + 1% acidifier + 1.2% inulin), T3 (RK + 1% acidifier + 0.5% papain enzyme), and T4 (RK + 1% acidifier + 1.2% inulin + 0.5% papain enzyme). Parameters measured included heterophiles, lymphocytes, leukocytes, and total plasma protein. Data were analyzed using variance at the 5% level and Duncan's test of significant differences at the 5% level. The results showed that the addition of acidifier with inulin and papain enzymes had a significant effect (p<0.05) on the differential leukocytes (heterophiles, lymphocytes, leukocytes, and total plasma protein). The conclusion is that the addition of 1% acidifier + 1.2% inulin + 0.5% papain enzyme (T4) can maintain the health condition of the body, as observed from the differential leukocytes in male turkeys during the growth period.